Out of the Ordinary. - Lewis, Helen (New Statesman, 2016)
The article examines the gender pay gap in Great Britain, focusing on how jobs seemingly become less prestigious when the workforce is primarily female. It suggests this indicates that encouraging more women to enter male-dominated professions to address the pay gap won't result in changes. Particular attention is given to wage differences among older women with children and their male counterparts.